2007
DOI: 10.1086/518864
|View full text |Cite
|
Sign up to set email alerts
|

The Fifth Data Release of the Sloan Digital Sky Survey

Abstract: This paper describes the Fifth Data Release (DR5) of the Sloan Digital Sky Survey (SDSS). DR5 includes all survey quality data taken through June 2005 and represents the completion of the SDSS-I project (whose successor, SDSS-II will continue through mid-2008). It includes five-band photometric data for 217 million objects selected over 8000 square degrees, and 1,048,960 spectra of galaxies, quasars, and stars selected from 5713 square degrees of that imaging data. These numbers represent a roughly 20% increme… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
274
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 648 publications
(274 citation statements)
references
References 49 publications
0
274
0
Order By: Relevance
“…We use photometric and spectroscopic coverage from the sixth data release (DR6) of the Sloan Digital Sky Survey (SDSS; see York et al 2000;Stoughton et al 2002;Adelman-McCarthy et al 2007, and references therein). The survey, not yet finished but nearing completion, will eventually cover 10, 000 deg 2 in the northern galactic cap and a smaller region on the celestial equator.…”
Section: Optical Surveys: Sdssmentioning
confidence: 99%
“…We use photometric and spectroscopic coverage from the sixth data release (DR6) of the Sloan Digital Sky Survey (SDSS; see York et al 2000;Stoughton et al 2002;Adelman-McCarthy et al 2007, and references therein). The survey, not yet finished but nearing completion, will eventually cover 10, 000 deg 2 in the northern galactic cap and a smaller region on the celestial equator.…”
Section: Optical Surveys: Sdssmentioning
confidence: 99%
“…If an object's colors fit well to a template then it is assumed to be a star. To get the widest wavelength range of data with which to make comparisons, we compile all available PQ UBRIriz (determined using the absolute calibration), SDSS ugriz (data release 5; see Adelman-McCarthy et al 2007), Galaxy Evolution Explorer (GALEX) fn (data release 3; see Martin et al 2005), and 2MASS JHK measurements (Skrutskie et al 2006) of the variables. The spectral templates published by A. J. Pickles (Pickles 1998), which span wavelengths of 1150-12500 Å, are convolved with the transmission curves of the various surveys and fitted to the broadband measurements.…”
Section: Color Classificationmentioning
confidence: 99%
“…These focused on characterizing the three-dimensional topology and showed that, depending on the considered scale, topology can be useful in constraining both cosmological parameters and the galaxy formation mechanism. For example, Park et al (2005a) characterized the topology of the SDSS main galaxy sample from the New York University Value-Added Galaxy Catalog (NYU-VAGC; Blanton et al 2005), which has similar sky coverage to SDSS Data Release 4 (DR4; Adelman-McCarthy et al 2006), and presented the first clear demonstration of luminosity dependence of galaxy clustering topology (i.e., brighter galaxies show a stronger signal of meatball topology); more recently, Gott et al (2009) measured the three-dimensional LSS topology of the SDSS DR4plus luminous red galaxy (LRG) sample from the NYU-VAGC (a subsample of SDSS DR5; Adelman-McCarthy et al 2007) and found strong consistency with Gaussianity of the primordial fluctuations. In the latter case, the large available sample size allowed topology to be an important tool for testing galaxy formation models.…”
Section: Introductionmentioning
confidence: 99%